Fluency and text comprehension: a systematic review - Hickmann, Girlane Moura (2021)
Fluent reading (reading with accuracy, speed, and prosody) is one of the skills that influence text comprehension. The aim of this paper was to identify, through a systematic review, empirical evidence of the relationship between fluency components and reading comprehension and the methods used in these studies. The method of this article consisted of a survey and analysis of works published and available entirely in the electronic databases ERIC, CAPES and Busca Integrada UFPR - Acervo SIBI. Of the 989 papers that returned from the electronic search, 64 of them were analyzed, of which 12 are in Portuguese and 52 in English. The studies analyzed show that there is  a positive relationship between fluency and comprehension of texts, few of which directly studied the reading with prosody.